Letermovir Administration to Prevent Cytomegalovirus Reactivation Is the Potential Risk of Chronic Graft-Versus-Host Disease in Patients Who Received Haploidentical Stem-Cell Transplantation With Post-Transplant Cyclophosphamide - Terao, Toshiki; Matsuoka, Ken-ichi; Narita, Kentaro; Tsushima, Takafumi; Yuyama, Satoshi; Kuzume, Ayumi; Tabata, Rikako; Miura, Daisuke; Takeuchi, Masami; Matsue, Kosei (Frontiers in Oncology, 2021)
The prevention of chronic graft-versus-host disease (cGVHD) is important for recipients of hematopoietic stem-cell transplantation (HSCT). As one of the etiologies, the relationship between early T-cell recovery and subsequent cGVHD development has been the focus of attention. Recently, letermovir (LTV) was approved for preventing cytomegalovirus (CMV) reactivation in the early transplantation phase. Although CMV affects the immune reconstitution after HSCT, the impacts of LTV to prevent CMV reactivation on early T-cell recovery and cGVHD have not been fully investigated. We aimed to identify early T-cell recovery under LTV at day 30 in 15 and 33 recipients from matched related donors (MRDs) and haploidentical donors with post-transplant cyclophosphamide (PTCy-haplo), respectively. Early increases in the levels of total lymphocytes and HLA-DR+ activated T-cells at day 30 were observed under CMV prophylaxis by LTV only in PTCy-haplo recipients and not in MRD recipients. Moreover, PTCy-haplo recipients with LTV showed a significantly higher incidence of cGVHD, but not acute GVHD. Our observations suggest that an early increase in the levels of HLA-DR+ activated T-cells may be implicated in the development of cGVHD in patients treated with PTCy who received LTV. Further studies are warranted to validate our results and elucidate the detailed mechanisms of our new insights.